Innovation of Entrepreneurship Projects on The Quality of Islamic Education The Independent Learning (Merdeka Belajar) Curriculum: Case Study at SMKN 1 Pedan - Nugraheni, Aisah Dian; Inayati, Nurul Latifatul (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Quality education is education that is carried out through several processes in realizing and developing the quality of students in ignorance of the learning process. To achieve a high quality education, it is necessary to have innovations in an education by paying attention to innovation, one of which is from the curriculum. The method used in this research is through interview techniques which are carried out using a phenomenological qualitative approach. The object of this research is the deputy head of school in the field of curriculum and Islamic religious education teachers and students. The source used is data from interviews. The results of this study are that Freedom to Learn is something new in schools in general for all teachers. with the new curriculum guided to learn but in the independent curriculum both teachers and students have the teacher's discretion in determining learning methods. This means that teachers are given the opportunity to innovate in developing learning materials and techniques. The concept of teaching and learning that provides more space for creativity and innovation in the learning process at madrasas. Strengthening the character of the Pancasila student profile Rahmatan Lil Alamin in the learning process which is highlighted. The conclusion is that in the independent learning curriculum, all schools, both students and teachers, are required to always learn and innovate because this curriculum emphasizes aspects and direct learning experiences to develop the talents possessed by students.Keywords : Innovation, Curriculum Freedom of Learning (Merdeka Belajar), Quality Of Islamic Education.